2021
DOI: 10.3390/diagnostics11020331
|View full text |Cite
|
Sign up to set email alerts
|

Pyonephrosis Ultrasound and Computed Tomography Features: A Pictorial Review

Abstract: Urinary tract infections (UTIs) are the most frequent community-acquired and healthcare-associated bacterial infections. UTIs are heterogeneous and range from rather benign, uncomplicated infections to complicated UTIs (cUTIs), pyelonephritis and severe urosepsis, depending mostly on the host response. Ultrasound and computed tomography represent the imaging processes of choice in the diagnosis and staging of the pathology in emergency settings. The aim of this study is to describe the common ultrasound (US) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Patodia et al studied a group of 91 patients with pyonephrosis and 410 patients without pyonephrosis and revealed that there are risk factors that increase the incidence of pyonephrosis including the stone size, the severity of hydronephrosis, the time of presentation, and the function of the kidney [6]. Our results corroborate some of these findings (although not the same points of evaluation in our study), where we found that The two leading causes of pyonephrosis are obstruction and infection; hence any risk factor increasing the incidence of urinary tract infections (UTI) could also lead to pyonephrosis [7]. In our study, we found that patients with pyonephrosis had comorbid conditions (especially diabetes in 38% of cases), and they were more frequently of the female gender compared to those seen in the hydronephrosis group (61.5% vs 38.5%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Patodia et al studied a group of 91 patients with pyonephrosis and 410 patients without pyonephrosis and revealed that there are risk factors that increase the incidence of pyonephrosis including the stone size, the severity of hydronephrosis, the time of presentation, and the function of the kidney [6]. Our results corroborate some of these findings (although not the same points of evaluation in our study), where we found that The two leading causes of pyonephrosis are obstruction and infection; hence any risk factor increasing the incidence of urinary tract infections (UTI) could also lead to pyonephrosis [7]. In our study, we found that patients with pyonephrosis had comorbid conditions (especially diabetes in 38% of cases), and they were more frequently of the female gender compared to those seen in the hydronephrosis group (61.5% vs 38.5%).…”
Section: Discussionsupporting
confidence: 90%
“…However, differentiation of simple hydronephrosis from pyonephrosis may be difficult on CT as it is mostly diagnosed by the presence of indirect signs. The imaging of obstruction can be performed with NCECT with an accuracy of 97% in the detection of stones within the ureters, although contrast-enhanced CT scans are more suitable to detect infection, in addition to any parenchymal or functional changes [7].…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal fluid in non-traumatic patients may be the expression of inflammatory diseases and infection and can be either free or organized. Free fluid around parenchymas and viscera is the expression of a complicated pathology or an extra-visceral extension of the disease where free fluid can stand next to the affected organ or organize into infected collections [ 25 , 26 ] ( Figure 3 and Figure 5 ).…”
Section: Black: Us Featuresmentioning
confidence: 99%
“…The diagnostic capability of US in characterizing fluid components is comparable to MR imaging. US can differentiate transudative, exudative, and complex fluid components such as debris and fluid/fluid levels [ 8 , 25 , 52 ]. The presence of heterogeneous fluids within the vessels, the urinary tract, or the biliary system can rapidly orient the diagnosis ( Table 2 ).…”
Section: Black: Us Featuresmentioning
confidence: 99%
See 1 more Smart Citation